2007
DOI: 10.1007/s10753-007-9026-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of T0901317 on Hepatic Proinflammatory Gene Expression in ApoE−/− Mice Fed a High-fat/high-cholesterol Diet

Abstract: The synthetic LXR agonist T0901317 has paradoxical roles in hepatic gene expression of proinflammatory cytokines in apoE-/- mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 40 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…In contrast, the T0901317-induced increase in cholesterol in apoE 2/2 was in HDL and accompanied by a marked increase in apoA1, but not ApoB levels (20). Interestingly, the apolipoprotein composition and size of the T0901317-induced particle in E3L is comparable to that induced by T0901317 in C57/Bl6 mice which was designated "enlarged HDL" (22).…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, the T0901317-induced increase in cholesterol in apoE 2/2 was in HDL and accompanied by a marked increase in apoA1, but not ApoB levels (20). Interestingly, the apolipoprotein composition and size of the T0901317-induced particle in E3L is comparable to that induced by T0901317 in C57/Bl6 mice which was designated "enlarged HDL" (22).…”
Section: Discussionmentioning
confidence: 90%
“…Plasma HDL cholesterol levels are negatively related to cardiovascular disease events [34] . Although LXR activation increases the plasma levels of HDL, it promotes the TG synthesis and leads to hyperlipidemia, which is an independent risk factor of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Liver X receptors and (LXR and LXR ) are ligand-activated transcription factors involved in the control of lipid metabolism and inflammation. Recently, studies from our laboratory reported that synthetic LXR agonists could inhibit the progression of atherosclerosis in apoE / mice fed a highfat/high-cholesterol diet [13][14][15] . The endogenous activators of these receptors are oxysterols and intermediates in the cholesterol biosynthetic pathway.…”
Section: Introductionmentioning
confidence: 99%